Probiotics in Irritable Bowel Syndrome: An Up-to-Date Systematic Review - Dale, Hanna Fjeldheim (Nutrients, 2019)
Irritable bowel syndrome (IBS) is a frequent functional gastrointestinal disorder, and alterations in the gut microbiota composition contributes to symptom generation. The exact mechanisms of probiotics in the human body are not fully understood, but probiotic supplements are thought to improve IBS symptoms through manipulation of the gut microbiota. The aim of this systematic review was to assess the latest randomized controlled trials (RCTs) evaluating the effect of probiotic supplementation on symptoms in IBS patients. A literature search was conducted in Medline (PubMed) until March 2019. RCTs published within the last five years evaluating effects of probiotic supplements on IBS symptoms were eligible. The search identified in total 35 studies, of which 11 met the inclusion criteria and were included in the systematic review. Seven studies (63.6%) reported that supplementation with probiotics in IBS patients significantly improved symptoms compared to placebo, whereas the remaining four studies (36.4%) did not report any significant improvement in symptoms after probiotic supplementation. Of note, three studies evaluated the effect of a mono-strain supplement, whereas the remaining eight trials used a multi-strain probiotic. Overall, the beneficial effects were more distinct in the trials using multi-strain supplements with an intervention of 8 weeks or more, suggesting that multi-strain probiotics supplemented over a period of time have the potential to improve IBS symptoms.